Nanotermites multicamadas de Al/NiO sintetizadas por Magnetron Sputtering - Santos, Tadeu Henrique dos (2017)
Explosives, propellants and pyrotechnics are known as energetic materials, which release a large amount of energy from a stimulus, which can be electric, mechanical, luminous, thermal, etc. The use of nanostructured reagents in thermally formed compositions leads to a higher degree of interaction between the particles, improving the ignition and release properties of these compounds. In this work, nanostructured thermites, also called nanothermites, were synthesized and characterized in the form of multilayer thin films, synthesized by magnetron sputtering of Al / NiO with different stoichiometries. Some compositions have shown released amount of heat of about 1.7 kJ /g, which is somewhat below the maximum achieved by similar compositions, which is around 2.44 kJ /g (YAN et al., 2015). The heat released by the thermitic reaction is dependent on the deposition parameters. Some films were found to be different and this was attributed to some factors, such as variations in the DC cathode current, which caused little deposition of aluminum in some layers. This type of nanostructured reactive material can provide a future use in semiconductor electronic structures, producing high energy density in a compact source, with potential uses in micropropulsion for space devices, controlled ignition systems for ammunition firing, among other applications.